DET SEMANTISKT GEMENSAMMA OMRÅDET SOM ANALYSMEDEL FÖR METAFORISKA UTTRYCK - Turunen, Mikko (K&K - Kultur og Klasse, 2013)
COMMON SEMANTIC GROUND AS AN AID IN ANALYSING METAPHORICAL EXPRESSIONS | This paper discusses the metaphorical properties of language and the various manifestations of those properties. I set the stage by discussing the central issues of research into metaphorical expressions. I then proceed to introduce my concept of common semantic ground based on the various scientific views on metaphors. I also provide concrete examples on how my concept can be structured into graphical representations. The common semantic ground is based on two concepts: the overlapping fields of meanings in the metaphorical expressions, and the idea of similarity, which is established through analogies in the contrasted phenomena. A well-established paradigm about the relationship between the vehicle and tenor exists in the study of metaphor, but there have been few attempts to establish patterns of analysis in the study of metaphorical properties of a language. As I outline in my article, the vehicle and tenor are conjoined by their overlapping fields of meanings, which I call the common semantic ground. This common ground contains those elements from both the source and target domains that enable both a meaningful connection and the mapping between the two domains. As a method, the common semantic ground serves the analysis of constructing a metaphor’s meaning. It can also be used as a means to argument thematic interpretations via the different layers of the component parts in the imagery.